2017
DOI: 10.3928/01477447-20170120-04
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction Reporting After Total Hip Arthroplasty: A Systematic Review

Abstract: This review evaluated the quality of patient satisfaction reporting after total hip arthroplasty. The initial search of the MEDLINE database yielded 755 studies. Twenty-four met the inclusion criteria. Most studies provided level III or IV evidence (n=15, 62.5%). The most common method used to assess satisfaction was the 10-point visual analog scale (7 studies, 29.2%), followed by an ordinal satisfaction scale (6 studies, 25.0%). The quality of evidence was poor, and the methods used to assess satisfaction wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 46 publications
(72 reference statements)
0
13
1
2
Order By: Relevance
“…A recent review of hip arthroplasty satisfaction reporting limited to US literature found a similar problem with variable methods of reporting patient satisfaction [ 11 ]. In the hip literature, the most commonly used reporting method was a numeric 0–10 scale for overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of hip arthroplasty satisfaction reporting limited to US literature found a similar problem with variable methods of reporting patient satisfaction [ 11 ]. In the hip literature, the most commonly used reporting method was a numeric 0–10 scale for overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is considered one of the most successful surgical procedures in modern medicine. 1 Treatment goals include pain relief, restoration of normal hip biomechanics and improvement in function. 1 The success of THA is well documented, with high patient satisfaction rates, low morbidity rates and cost-effective surgery.…”
Section: Introductionmentioning
confidence: 99%
“…1 Treatment goals include pain relief, restoration of normal hip biomechanics and improvement in function. 1 The success of THA is well documented, with high patient satisfaction rates, low morbidity rates and cost-effective surgery. 2 Most of these publications come from THA performed in high-volume arthroplasty units, done in high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have noted that over 80% of patients indicate they are satisfied following THA [37, 38]. Studies have demonstrated similar patient satisfaction following primary hip arthroscopy [21, 22, 39, 40].…”
Section: Discussionmentioning
confidence: 99%